Investigating the causal relationship between ankylosing spondylitis and osteoporosis in the European population: a bidirectional Mendelian randomization study - Mei, Jian; Hu, Hongxin; Ding, Haiqi; Huang, Ying; Zhang, Wenming; Chen, Xiaoqing; Fang, Xinyu (Frontiers in Immunology, 2023)
BACKGROUND: Ankylosing Spondylitis (AS) can often complicate with osteoporosis (OP), but it is unknow whether there is a genetic causal effect of AS on OP or vice versa. Therefore, we conducted a bidirectional Mendelian randomization (MR) analysis to determine the causal genetic association between AS and OP. METHODS: Bone mineral density (BMD) was used as a phenotype for OP. The AS dataset was from the IGAS consortium and included people of European ancestry (9,069 cases and 13,578 controls). BMD datasets were obtained from the GEFOS consortium, a large GWAS meta-analysis study, and the UK Biobank and were divided into five categories based on site (total body (TB): 56,284 cases; lumbar spine (LS): 28,498 cases; femoral neck (FN): 32735 cases; forearm (FA): 8,143 cases; heel: 265,627 cases) and five categories based on age (0-15: 11,807 cases; 15-30: 4,180 cases; 30-45: 10,062 cases; 45-60: 18,062 cases; over 60: 22,504 cases).To obtain the casual estimates, the inverse variant weighted (IVW) method was mainly used. The presence of heterogeneity was evaluated using the Cochran's Q test. Pleiotropy was assessed utilizing MR-Egger regression and MR-pleiotropy residual sum and outlier (MR-PRESSO). RESULTS: Generally, there were no significant causal associations between genetically predicted AS and decreased BMD levels. The results of MR-Egger regression, Weighted Median, and Weighted Mode methods were consistent with those of the IVW method. But there was a sign of a connection between genetically elevated BMD levels and a decreased risk of AS (Heel-BMD: OR = 0.897, 95% CI: 0.795-0.971, P = 0.012; Total-BMD: OR = 0.948, 95% CI: 0.907-0.990, P = 0.017; LS-BMD: OR = 0.919, 95% CI: 0.861-0.980, P = 0.010). The results were confirmed to be reliable by sensitivity analysis. CONCLUSION: This study found that the causal association between genetic liability to AS and the risk of OP or lower BMD was not evident, highlighting the second effect (e.g., mechanical reasons such as limited mobility) of AS on OP. Simultaneously, a possible link between genetically predicted BMD and AS susceptibility was identified, suggesting the potential for the development of new diagnosis and therapeutic strategies for AS via OP-related pathways.